GAMBARAN PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG PERUBAHAN FISIK PUBERTAS DI SMPN 3 TEMBILAHAN HULU - Nurhidayah; Oktaviani (STIKES HUSADA GEMILANG, 2020)
A teenager's ignorance of the changes that occur in him and why it happens can cause anxiety and embarrassment. They will ask if change is normal, if everyone is experiencing it and what they should do with it. Because of the increasing interest of adolescents in the problem of changes that occur in them, teenagers try to find various information about the changes experienced. This will lead to risky attitudes and behaviors if adolescents get information about reproductive health that is not appropriate. This study aims to find out the picture of knowledge and attitudes of young women about the physical changes of puberty in SMPN 3 Tembilahan Hulu in 2019. This study is descriptive, data collection using questionnaires with the method of spreading questionnaires directly to respondents. Sampling using stratified random sampling technique with proportionate stratified sampling type with a sample number of 99 students. The results of this study found that most respondents had sufficient knowledge about the physical changes of puberty as much as (51%), and most respondents had as many negative attitudes towards the physical changes of puberty (54%). Based on the results of the study, it is expected that the education can provide counseling and motivation to students to get a briefing of knowledge, especially about the physical changes of puberty so that adolescents know about the physical changes of puberty in adolescents.